Cooccurence of Volatile Substance Positivity and Ischaemic Cardiac Disease Case Report - Ersoy, Gökhan; Arslan, Murat Nihat; Pakiş, Işıl; Üzün, İbrahim (The Bulletin of Legal Medicine, 2009)
Volatile substance abuse is a major problem, especially in teens. It is a popular recreational activity among young population. Beside this, there is a group, which uses the substances for 10-20 years. Case is 37 years old man without volatile substances history from his parent. It was very easy to smell an odor like “industrial thinner” during the autopsy. There were an obvious ischemic cardiac disease and toxicologic screening was corrected the suspects about volatile substances occurrence. Cardiac toxicity is the leading cause for the death attributing the volatile substances. They may cause ventricular fibrillation or other rhythm disturbances and coronary vasospasm. Therefore, it may create a synergic effect to use a volatile on the ground of ischemic cardiac disease. It would be easier to decide to cause of death if medical examiner obtain sufficient medical and legal history. Toxicologic screening must be done separately for blood, urine, lung, brain and kidney and reports must show quantitative results if possible. Key words: Forensic Pathology, toxicology, autopsy, arrhythmia, coronary disease